1995
DOI: 10.1002/j.2161-007x.1995.tb00386.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cross‐Cultural Comparison of the Worldviews of American, Chinese (From Taiwan), and Irish Graduate Counseling Students and Implications for Counseling

Abstract: This study compares the worldviews of 64 American, 37 Chinese, and 29 Irish graduate counseling students on the Scale to Assess World Views (SAWV; Ibrahim & Kahn, 1987). All of the students were master's students at universities in their respective countries. Results indicated that the Chinese were more individualistic than were either the Americans or the Irish, whereas the Irish saw human nature as more good than either the Chinese or the Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…They reported that Japanese participants expected a single pool shot to have a greater impact on a distal shot (e.g., the sixth shot after the focal shot) and a distal event (e.g., overall outcome of the game) than the European American participants. The results support the view that East Asians are more long-term oriented and forward-looking than Americans are (Briley, 2009;Cheng, O'Leary, & Page, 1995;Hofstede, 2001; but see Graham, 1981;Kluckhohn & Strodtbeck, 1961). Likewise, Shechter, Durik, Miyamoto, and Harackiewicz (2011) found that East Asians were more motivated to learn a technique that could help them with long-term or distal goals than proximal goals.…”
Section: Culture and Temporal Information Focussupporting
confidence: 78%
See 1 more Smart Citation
“…They reported that Japanese participants expected a single pool shot to have a greater impact on a distal shot (e.g., the sixth shot after the focal shot) and a distal event (e.g., overall outcome of the game) than the European American participants. The results support the view that East Asians are more long-term oriented and forward-looking than Americans are (Briley, 2009;Cheng, O'Leary, & Page, 1995;Hofstede, 2001; but see Graham, 1981;Kluckhohn & Strodtbeck, 1961). Likewise, Shechter, Durik, Miyamoto, and Harackiewicz (2011) found that East Asians were more motivated to learn a technique that could help them with long-term or distal goals than proximal goals.…”
Section: Culture and Temporal Information Focussupporting
confidence: 78%
“…Additional research on cultural perception of the future has shown that East Asians perceive the future to be more proximal to the present than European Americans (Lee, Lee, & Kern, 2011). The results support the view that East Asians are more long-term oriented and forward-looking than Americans are (Briley, 2009;Cheng, O'Leary, & Page, 1995;Hofstede, 2001; but see Graham, 1981;Kluckhohn & Strodtbeck, 1961).…”
Section: Culture and Temporal Information Focusmentioning
confidence: 63%
“…For example, in teaching how and when to use an appropriate statistic, a widely used methodology is to teach specific statistical techniques with examples from the literature that illustrate the correct statistical choice (Huck & Cormier, 1996). This method can readily accommodate studies with spiritual content by referencing recent research (analysis of variance [ANOVA] in Cheng, O'Leary, & Page, 1995;Johnson & Ridley, 1992; ANOVA and t test in Rayburn, 1991;chi-square in Roffey & Porter, 1992;correlation in Schwehn & Schau, 1990). Similarly, studies with spiritual and religious content are available that illustrate preexperimental, quasi-experimental, and experimental designs; examples include Hatcher and Underwood (1990), McCullough and Worthington (1995), Morrow, Worthington, and McCullough (1993), Richards, Owen, and Stein (1993).…”
Section: Research and Program Evaluationmentioning
confidence: 99%